Modeling study of stress generation of a single active material particle connected to solid electrolyte in solid-state batteries. (20th January 2022) - Lee, Yoon Koo; Shin, Hosop
Highlights: We established a single particle model to study stress generation of active particles surrounded by solid electrolytes at different locations. Non-uniform Li-ion concentration and stress inhomogeneity are observed in active particles connected to solid electrolytes. The direction and magnitude of the stress change significantly depending on the location of AM, solid electrolyte, and their interfaces. Fracture probability at the active material/solid electrolyte interface is largely determined by the Young's modulus ratio of AM to SE. Abstract: One of the major problems with solid-state batteries (SSBs) is the mechanical degradation of the interfacial structures between active materials (AMs) and solid electrolytes (SEs). In this study, we established a single particle model to study stress generation of AM particles surrounded by SEs and their impact on the mechanical degradation of SSBs including Li7 La3 Zr2 O12 (LLZO) or Li10 GeP2 S12 (LGPS). When the AM particle was constrained by the SE, the first principal stress of the AM particle was significantly higher than that of the AM particle in the liquid electrolyte. The changes in the direction and magnitude of the stress strongly depended on the locations of the AM/SE. The largest change in the stress was often observed in the interface of the SE and the trend is dependent on the Young's modulus ratio of AM to SE. Because the interface between the AM and SE experiences the most significant mechanical degradation, it is crucial to find the optimal combination of AMs and SEs based on the mechanical properties for the design of SSBs to reduce the probability of failure. Moreover, we investigated the effect of the material properties, porosity, and contact area between AMs and SEs on the lithium transport and stress evolution. To minimize the mechanical degradation of SSBs, it is necessary to increase the AM/SE contact ratio and to achieve homogeneous AM particle distribution that enables a higher local volume fraction of SE. The results of this study can provide valuable insights into the fracture behavior of SSBs and guide the electrode design to minimize the mechanical degradation. Graphical abstract: Image, graphical abstract